Awareness Regarding Anesthesiology and Anesthesiologists Among General Population in Developing Country- A Cross Sectional Survey - Khyati Pandya; Kamla H Mehta; Kirti D Patel (Medsci Publications, 2016)
Background: Anaesthesiologists are playing decisive role in pa- tient management. Nowadays, they are involved in pain clinic and critical care also but the general public know little about them. So this study was undertaken to assess the perception of general population from poor socioeconomic area regarding the anaesthe- siology and role of anaesthesiologists. Methods: The study was carried out at Shardaben Hospital, Saraspur, in 200 participants, between the age group of 18-75 yrs of age to assess their knowledge regarding anaesthesiology and anaesthesiologists. A questionnaire containing three parts was filled by asking each question one by one in Guajarati or Hindi. The collected data analysed with SPSS software 17. Results: In our study population, 6.5% were HSC passed and 58.5% were SSC pass. While 24.5% were illiterate and only 10.5% were graduate pass. Only 26% of participants were known about anaesthesiology and role of anaesthesiologists. Conclusion: Results of study showed that the wide spread igno- rance and misconceptions about anaesthesiology and anaesthesi- ologists are still prevalent in general population and these are more in poor socioeconomic area.